Bioconversion of sisal agro-industrial waste into high protein oyster mushrooms. (June 2021) - Oliveira do Carmo, Cristiano; Mota da Silva, Rafael; de Souza Rodrigues, Marcos; Fermino Soares, Ana Cristina
Abstract: This study evaluated the production of P. ostreatus mushrooms on substrates formulated with different proportions of sisal ( Agave sisalana Perrine) shredded leaf (SSL) and dry fiber powder (DFP) waste, with 5% wheat-bran and 3% triturated charcoal. The substrates were fully colonized at 16 to 18 days, primordia formation started at 20 to 21 days after inoculation, and the complete production cycle of P. ostreatus occurred within 55 days. The substrate with 70% SSL and 30% DFP was the most effective, with biological efficiency of 79.9%, and mushroom yield of 260.2 g kg −1 of fresh substrate. Mushrooms with 29.0% crude protein and 2.2% fat were produced. Sisal fiber agro-industrial waste can be efficiently bioconverted into nutrient rich oyster mushrooms. This bioprocess can generate opportunities for the creation of additional income for small family-run farms in sisal producing countries, and prevent the inappropriate waste disposal on farms. Graphical abstract: Unlabelled Image Highlights: Sisal leaf shredding and fiber waste as substrate for efficient mushroom growth Biological efficiency of 79.9% for Agave sisalana waste bioconversion into mushrooms Oyster mushrooms with 29% protein and 2.2% fat were produced from sisal fiber waste. Bioconversion of sisal waste into mushrooms can boost income and reduce poverty.